CELLULAR ENERGY METABOLISM DURING FETAL DEVELOPMENT : II. Fatty Acid Oxidation by the Developing Heart - Warshaw, Joseph B. (The Rockefeller University Press, 1970)
In view of the importance of fatty acids as substrates for the mature heart, fatty acid oxidation by fetal and calf heart mitochondria has been investigated. Free fatty acids of 10 carbon units or less which exhibit carnitine-independent transport into mitochondria were effective substrates for oxidative phosphorylation in both fetal and calf heart mitochondria. Efficient oxidative phosphorylation with these substrates was dependent upon the presence of bovine serum albumin in the assay medium to reverse the uncoupling effects of the fatty acids. In the presence of bovine serum albumin, ADP/0 ratios were in the range of 3 when short-chain fatty acids and carnitine esters of short- and long-chain fatty acids were substrates. Compared with calf heart mitochondria, fetal heart mitochondria showed decreased carnitine-dependent oxidation of palmityl-CoA. However, the oxidation of palmitylcarnitine was identical in both. These data suggest that the formation of palmitylcarnitine is rate limiting for palmityl-CoA oxidation by the fetal heart mitochondria and that long-chain fatty acids are not readily oxidized by the fetal heart.